Kajian Kecukupan dan Kompetensi Personel Bandara UPT Kelas Utama Han Nadim – Batam - Juanda Siahaan (Research and Development Agency of The Ministry of Transportation, 2011)
Flight conditions in Indonesia is currently experiencing very significant growth. In accordance with the terms of the aviation world, which is changing around the world in turn requires increasing the competence of human resources in the field of aviation. Human resources competence of aviation (airport personnel) is an important part in supporting aviation safety, it is a key requirement in the implementation of aviation services suppressing the accurence of aviation accidents.Systems and procedures, competence technicians, adequate facilities and support a favorable working environment in one Sigle unit. Therefore the adequacy of human resources personnel who operate and maintain facilities that have licensed some of these officers have not had licensed/ceriificate of competency, than the minimum requirements of human resources.